Novel biocompatible magnetoelectric MnFe2O4 core@BCZT shell nano–hetero-structures with efficient catalytic performance - Chernozem, Roman V.; Urakova, Alina O.; Chernozem, Polina V.; Koptsev, Danila A.; Mukhortova, Yulia R.; Grubova, Irina Yu; Wagner, Dmitriy V.; Gerasimov, Evgeny Yu; Surmeneva, Maria A.; Kholkin, Andrei L.; Surmenev, Roman A. (Small)
Magnetoelectric (ME) small-scale robotic devices attract great interest from the scientific community due to their unique properties for biomedical applications. Here, novel ME nano hetero-structures based on the biocompatible magnetostrictive MnFe2O4 (MFO) and ferroelectric Ba0.85Ca0.15Zr0.1Ti0.9O3 (BCZT) are developed solely via the hydrothermal method for the first time. An increase in the temperature and duration of the hydrothermal synthesis results in increasing the size, improving the purity, and inducing morphology changes of MFO nanoparticles (NPs). A successful formation of a thin epitaxial BCZT-shell with a 2–5 nm thickness is confirmed on the MFO NPs (77 ± 14 nm) preliminarily treated with oleic acid (OA) or polyvinylpyrrolidone (PVP), whereas no shell is revealed on the surface of pristine MFO NPs. High magnetization is revealed for the developed ME NPs based on PVP- and OA-functionalized MFO NPs (18.68 ± 0.13 and 20.74 ±0.22 emu g−1, respectively). Moreover, ME NPs demonstrate 95% degradation of a model pollutant Rhodamine B within 2.5 h under an external AC magnetic field (150 mT, 100 Hz). Thus, the developed biocompatible core–shell ME NPs of MFO and BCZT can be considered as a promising tool for non-invasive biomedical applications, environmental remediation, and hydrogen generation for renewable energy sources.